The perfect spin injection in silicene FS/NS junction - Tian, H.-Y.; Xu, N.; Luo, G.; Ren, Ch.-D. (Condensed Matter Physics, 2017)
We theoretically investigate the spin injection from a ferromagnetic silicene to a normal silicene (FS/NS), where the magnetization in the FS is assumed from the magnetic proximity effect. Based on a silicene lattice model, we demonstrated that the pure spin injection could be obtained by tuning the Fermi energy of two spin species, where one is in the spin orbit coupling gap and the other one is outside the gap. Moreover, the valley polarity of the spin species can be controlled by a perpendicular electric field in the FS region. Our findings may shed light on making silicene-based spin and valley devices in the spintronics and valleytronics field. Теоретично вивчається спiнова iнжекцiя з феромагнiтного силiцену в нормальний силiцен (FS/NS перехiд), коли намагнiченiсть в FS припускається з магнiтного ефекту близькостi. На основi граткової моделi силiцену показано, що чисто спiнова iнжекцiя може бути отримана пiдлаштуванням енергiй Фермi спiнiв двох сортiв, коли один сорт є в зонi спiн-орбiтальної взаємодiї, а iнший поза зоною. Крiм того, долинова полярнiсть спiнових сортiв може контролюватися перпендикулярно напрямленим електричним полем в FS областi. Нашi результати можуть пролити свiтло на створення на основi силiцену спiнових i долинових пристроїв для спiноелектронiки i велiтронiки.